2001
DOI: 10.1159/000055720
|View full text |Cite
|
Sign up to set email alerts
|

Endonasal Endoscopic Dacryocystorhinostomy in a Four-Month-Old Infant

Abstract: The authors present a case of endonasal endoscopic dacryocystorhinostomy in a 4-month-old girl suffering from remarkable epiphora, persistent bulging and recurrent abscesses in the medial canthal region of the left eye. All conservative therapeutic attempts failed. Several external incisions were performed in order to solve the acute phases of the inflamed lacrimal sac. The procedure was performed by means of otologic microsurgical instruments under endoscopic control. No silicone stent was used. Ten months af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…We believe that an endonasal approach can be successfully carried out without any complications in children younger than 1 year. Mladina et al 9 reported a EDCR performed in 4‐month‐old child. We performed the surgery in six children under 1 year of age with severe dacryocystitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that an endonasal approach can be successfully carried out without any complications in children younger than 1 year. Mladina et al 9 reported a EDCR performed in 4‐month‐old child. We performed the surgery in six children under 1 year of age with severe dacryocystitis.…”
Section: Discussionmentioning
confidence: 99%
“…Dacryocystitis and epiphora at the pediatric age are usually cured with conservative medical therapy, massage, antibiotics, probing, and silicone intubation, if necessary, and these are usually effective. [1][2][3][4][5][6][7][8][9] Dacryocystorhinostomy (DCR) is only seldom needed in recalcitrant cases and some traumatic injuries. 2,3,6,7,10 -12 We report our experience with endonasal DCRs (EDCRs) in 34 procedures.…”
Section: Introductionmentioning
confidence: 99%